2016
DOI: 10.30957/lingua.v13i2.180
|View full text |Cite
|
Sign up to set email alerts
|

Campur Kode Pada Pidato Presiden Sby Dalam Perayaan Hut Ke-69 Republik Indonesia

Abstract: Abstract:This study aims to identify code mixing used by the late President Susilo Bambang Yudhoyono (SBY) in his speech delivered in the 69th Indonesian Indepence Day. This study used content analysis implementing qualitative approach. A text of the official speech issued by the presidential office was used as sources of data. Corpora in the text was identified and classified as they were presented as code mixing in the social interaction contexts. This study revealed (1) 11 code mixings were present in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Dengan adanya lebih dari 1 bahasa dalam sebuah komunitas, maka masyarakat dari kepulauan banggai dapat menggunakan dua bahasa (bilingual) atau lebih. Yastanti (2016) Mesikpun campur kode umunya tejadi pada konteks yang informal, perlu diingat bahwa ciri kedua dari sebuah fenomena campur kode adalah terjadi secara natural (tidak wajib). Percakapan 4 dan 5 menunjukkan ciri kedua dari fenomena tersebut.…”
Section: Menurutunclassified
“…Dengan adanya lebih dari 1 bahasa dalam sebuah komunitas, maka masyarakat dari kepulauan banggai dapat menggunakan dua bahasa (bilingual) atau lebih. Yastanti (2016) Mesikpun campur kode umunya tejadi pada konteks yang informal, perlu diingat bahwa ciri kedua dari sebuah fenomena campur kode adalah terjadi secara natural (tidak wajib). Percakapan 4 dan 5 menunjukkan ciri kedua dari fenomena tersebut.…”
Section: Menurutunclassified
“…Fromkin, Rodman, & Hymas in (Yastanti, 2016), "Bilingualism (or multilingualism) also refers to the situation in nations in which two (or more) languages are spoken and recognized as official or national languages." It can be shown that bilingualism or multilingualism are two more languages used in a country as the official and national languages.…”
Section: Definition Of Bilingualismmentioning
confidence: 99%
“…From the statement, codeswitching two languages or more happens in a sentence on some variations. (Yastanti, 2016), "Code mixing occurs when a conversation uses both languages together to the extent that they change from one language to another in the course of a single utterance" means Code mixing occurs when there is a conversation that uses two languages so will change the meaning of the language.…”
Section: Definition Of Code Switching and Code Mixingmentioning
confidence: 99%